Community Transmission via Indirect Media-To-Person Route: A Missing Link in the Rapid Spread of COVID-19 - Hu, Qunfang; He, Lei; Zhang, Ying (Frontiers in Public Health, 2021)
To prevent the spread of coronavirus disease 2019 (COVID-19), stringent quarantine measures have been implemented so that health people and virus carriers have isolated themselves in the same community owing to the limit capacity of healthcare facilities. With the exponential growth of the infected population, the residential environment is contaminated by fomites from the infected residents and consequently threating the health of susceptible residents. Till now, little has been acknowledged on this indirect transmission route and its role on community transmission. Here we address the impact of self-isolated virus carriers on the residential environment and elucidate the potential transmission pathways via contaminated environment in communities. We urge further investigation on the superspreading cases in communities and hope to arouse the attention to evaluate the potential risk of indirect transmission route as well as the corresponding control measures.